2018
DOI: 10.3390/su10040965
|View full text |Cite
|
Sign up to set email alerts
|

Natural Resources Curse in the Long Run? Bolivia, Chile and Peru in the Nordic Countries’ Mirror

Abstract: Abstract:The new estimates of the Maddison Project show that GDP per capita ratio at purchasing power parity (ppp) between Bolivia and Finland has changed from 0.68 ca. 1850 to 0.16 in 2015; similarly, that between Chile and Norway from 0.65 to 0.28. The aim of this article is to present a review of the literature and available quantitative evidence to understand how these extreme differences became possible between countries with similarly enormous natural resource endowments. Specifically, the article seeks … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 91 publications
0
12
0
2
Order By: Relevance
“…The study focuses on the 1850-1939 period given our interest in the roots of economic divergence. In effect, we have shown that economic divergence between these two regions (measured by the GDPpc) became evident just after the Great Depression (Ducoing et al, 2018). Nevertheless, we have proved that there was a constant diversification of the export basket in the case of the Nordics between 1850and 1939(Badia-Miró, Carreras-Marín, Navarro, & Peres-Cajías, 2020.…”
Section: -Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…The study focuses on the 1850-1939 period given our interest in the roots of economic divergence. In effect, we have shown that economic divergence between these two regions (measured by the GDPpc) became evident just after the Great Depression (Ducoing et al, 2018). Nevertheless, we have proved that there was a constant diversification of the export basket in the case of the Nordics between 1850and 1939(Badia-Miró, Carreras-Marín, Navarro, & Peres-Cajías, 2020.…”
Section: -Introductionmentioning
confidence: 79%
“…Both regions are natural resource abundant and adopted an export-led growth strategy in this period. Moreover, both were small open economies (Ducoing et al, 2018) that, at least initially, depended on foreign technologies. These regions diverged economically in the twentieth century: the Nordic countries converged to the most developed cluster and the Andean cluster remained among the laggards.…”
Section: -Introductionmentioning
confidence: 99%
“…Por suerte para los objetos de la investigación científica, para los historiadores económicos y la sociedad en general, existe una importante evidencia cuantitativa con respecto al precio del producto durante este periodo. (Wright, 2015;Ducoing et al, 2018), por lo que estamos en condiciones de poner en duda, o al menos relativizar, la afirmación de los periodistas del reciente precio "histórico". A la vez, los precios de los minerales estratégicos, en cuanto a la nueva (potencial) economía verde, generan una mayor atención hacia procesos anteriores de ciclos de altos valores para las commodities.…”
Section: R I S T I á N D U C O I N Gunclassified
“…In the literature review, on the other hand, when comparing the levels of economic growth between developed countries (e.g., Finland, Sweden and Norway) and developing economies (e.g., Bolivia, Chile and Peru), variables related to the mechanism of trade openness, the diversification of their exports in natural resources, the accumulation of human knowledge, and the differences in the institutional framework (the role of state and fiscal contract) have been considered as the main factors of explanation (Ducoing et al, 2018).…”
Section: The Role Of Human Capital and Trade Openness In Economic Growthmentioning
confidence: 99%